2020
DOI: 10.3126/jota.v3i1.31362
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Circularity: A Review to Assess the Opportunities and Challenges to Close Loop in Nepali Tourism Industry

Abstract: Tourism is one of the important sectors in Nepali economy and gains high priority from the government sector as well owing to its contribution in the economic, social and environmental front. Despite these benefits, the tourism sector comes with negative externalities, providing rationality for shift towards a more sustainable approach. Despite this, the circular economy is yet to gain recognition, both at the academic and industrial level in Nepal. Thus, this article aims to fulfill that gap by introducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…From an academic perspective, we have significantly expanded the research on CE challenges in tourism. While previous studies [20,21] have identified challenges mapped to 6 CECPs in total, our research has expanded this field by 28 CECPs for the tourism industry. Furthermore, the endeavor to make the general research on CECPs relevant for the tourism industry has a pioneering character.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From an academic perspective, we have significantly expanded the research on CE challenges in tourism. While previous studies [20,21] have identified challenges mapped to 6 CECPs in total, our research has expanded this field by 28 CECPs for the tourism industry. Furthermore, the endeavor to make the general research on CECPs relevant for the tourism industry has a pioneering character.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CE challenges in the tourism sector is a field that has been highly under-researched. During our work on the CECPs, we have only identified two articles studying CE challenges for the tourism industry [20,21]. However, these articles fall short in answering our research question in two main ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has shown that tourist businesses need to be flexible and ready for change. Many businesses will look for an increase in brand image while reducing the cost associated, and them moving away from a linear economy model towards the CE in tourism is the possible solution [ 110 ]. As Zhang and Tian [ 111 ] stated, in order to increase the competitiveness of the tourism industry, circular tourism must be the solution.…”
Section: Discussionmentioning
confidence: 99%
“…If we overcome these challenges and make the transition to a circular economy it will help to reunite environmental, social and economic perspectives in agriculture and support in achieving sustainable development goals. Furthermore, after the implementation of a circular economy model, they should be monitored regularly by developing proper sets of indicators (Aryal, 2020).…”
Section: Barriers For Circular Agriculturementioning
confidence: 99%